Task-Irrelevant Context Learned Under Rapid Display Presentation: Selective Attention in Associative Blocking - Zang, Xuelian; Assumpção, Leonardo; Wu, Jiao; Xie, Xiaowei; Zinchenko, Artyom (Frontiers in Psychology, 2021)
In the contextual cueing task, visual search is faster for targets embedded in invariant displays compared to targets found in variant displays. However, it has been repeatedly shown that participants do not learn repeated contexts when these are irrelevant to the task. One potential explanation lays on the idea of associative blocking, where salient cues (task-relevant old items) block the learning of invariant associations in the task-irrelevant subset of items. An alternative explanation is that the associative blocking rather hinders the allocation of attention to task-irrelevant subsets, but not the learning per se. The current work examined these two explanations. In two experiments, participants performed a visual search task either under a rapid presentation condition (300 ms) in Experiment 1, or under a longer presentation condition (2500 ms) in Experiment 2. In both experiments, the search items within both old and new displays were presented in two colors which defined the irrelevant and task-relevant items of each display. The participants were asked to search for the target in the relevant set in the learning phase. In the transfer phase the instructions were reversed and task-irrelevant items became task-relevant (and vice versa). In line with previous studies, task-irrelevant subsets resulted in no cueing effect post-transfer in the longer presentation condition. Most importantly, the same displays generated reliable cueing effects under the rapid presentation condition. Altogether these results demonstrate that under rapid display presentation attentional selection is global leading learning of global context. However, under a longer display presentation, global attention is blocked, leading to the learning of only the invariant relevant items in the learning session.